1997
DOI: 10.1046/j.1365-2249.1997.d01-960.x
|View full text |Cite
|
Sign up to set email alerts
|

VH genes expressed in peripheral blood IgE-producing B cells from patients with atopic dermatitis

Abstract: SUMMARYIn this study we analysed the V H genes expressed in IgE-producing peripheral B cells in two patients with severe atopic dermatitis. We found a diverse antibody repertoire containing V H genes of five different V H families, no V H 2 and 7 genes, with no biased usage of one particular V H gene family. Some V H germ-line segments were found to be used several times within the e transcripts (V3-23, V3-30).Comparison of the IgE-encoding V H genes with the respective germ-line elements revealed the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
(38 reference statements)
3
19
0
Order By: Relevance
“…An excessive usage of V H families that are normally infrequently used in secondary immune responses might hence be indicative of a superantigen-like activation of B cells (1). However, not all studies on immunogenetic characteristic of the IgE response in atopic eczema found a biased V H usage (7,8).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An excessive usage of V H families that are normally infrequently used in secondary immune responses might hence be indicative of a superantigen-like activation of B cells (1). However, not all studies on immunogenetic characteristic of the IgE response in atopic eczema found a biased V H usage (7,8).…”
Section: Discussionmentioning
confidence: 96%
“…Although some of these aspects have already been addressed in studies with adult patients [ (7)(8)(9), reviewed in Refs. 1 and 10], hitherto the molecular characteristics of the IgE response have not been analyzed systematically in children with atopic dermatitis, even though this specific age group is of particular interest for the evolvement of the IgE response in atopic dermatitis.…”
Section: Mmunoglobulin E Is a Central Effector Molecule In Allergymentioning
confidence: 99%
“…The selected patients exhibited serum IgE levels Ͼ200 IU/ml to ensure success in RT-PCR amplification of V H regions (27,33). Fifteen sequences were analyzed from the nasal biopsy samples of each patient.…”
Section: H Sequence Analysis and Ige ϩ B Cell Clonalitymentioning
confidence: 99%
“…With a new approach using V H family specific primers, the IgE V H repertoire of patients with allergic disease have been analyzed [12][13][14][15]. The dominance of V H 5 genes from asthma patients was observed [12,13], on the other hand, no bias for the usage of IgE V H was detected in AD patients [14].…”
Section: Introductionmentioning
confidence: 99%